The deconcentration of banking systems in Sub-Saharan Africa - (:unkn) unknown (My University, 2017)
This study brings to light a deconcentration of the banking systems of sub-Saharan African countries (SSA) over the period 2005-2015, in parallel with the rapid economic development of the continent during the super-cycle of rising commodity prices and the emergence of pan-African banking groups. The authors’ analysis shows that this trend is influenced, among other things, by the size of the market, the degree of international openness and the entry or exclusion of foreign banks. In addition, the lower the level of banking concentration, the higher the loan outstandings (as a percentage of GDP), which suggests that the level of competition between banks has a positive impact on credit distribution. However, banking concentration is only weakly linked to the quality of bank portfolios.
Keywords: African Research